Analisis Perbandingan Daya Output Serta Efisiensi Modul Surya Tanpa Menggunakan Reflektor dan Menggunakan Reflektor Atap Galvalum dan Aluminium Foil - Siahaan, David Soaloon; Stepanus; Purba, Robinson (Lektrokom : Jurnal Ilmiah Teknik Elektro, 2022)
Based on the location of Indonesian astronomy which is located on the equator, it is very appropriate or feasible if Indonesia develops PLTS as a technology to offset human demands for dependence on electricity. Indonesia also has a tropical climate (consisting of 2 seasons, hot and rainy), so that solar radiation in the territory of Indonesia (± 12 hours) is sufficient to make PLTS a solution for the demands of electricity needs. One of the technologies used in PLTS is solar panels. Solar panels are able to convert sunlight into electricity directly. The performance of solar panels is influenced by several factors, namely solar radiation, temperature and wind speed. Calculations and analysis of the measurement results show that the performance quality of solar cells is not very good, namely 0.143 for solar cells without reflectors, 0.156 for solar cells with galvalume roof reflectors and 0.157 for solar cells with aluminum foil reflectors. And the efficiency of solar cells without reflectors is 7.48%, for solar cells with galvalume roofs is 8.75%, and for solar cells with aluminum foil is 9.72%